2006
DOI: 10.1016/j.jtcvs.2006.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year results with the Hancock II valve: A multicenter experience

Abstract: Optimal 15-year durability can be expected in male patients 60 years and older who have undergone aortic valve replacement and in male patients 65 years and older who have undergone mitral valve replacement, extending safely the age limits for the use of this valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 16 publications
11
48
0
Order By: Relevance
“…Porcine bioprostheses implanted in the mitral position usually have lower durability than do their aortic counterparts, most likely because they are subjected to higher closing pressures. 3,5 We have shown that the MB has considerable resistance to SVD after MVR, which can be even superior to that of the MB in the aortic position-as observed by Riess and colleagues, 10 and more recently by our group. 11 However, the high mean age of our patients rendered us unable to explore the influence of age on MB durability, and therefore to extend the use of such a device to a younger population.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Porcine bioprostheses implanted in the mitral position usually have lower durability than do their aortic counterparts, most likely because they are subjected to higher closing pressures. 3,5 We have shown that the MB has considerable resistance to SVD after MVR, which can be even superior to that of the MB in the aortic position-as observed by Riess and colleagues, 10 and more recently by our group. 11 However, the high mean age of our patients rendered us unable to explore the influence of age on MB durability, and therefore to extend the use of such a device to a younger population.…”
Section: Discussionsupporting
confidence: 58%
“…This has been shown in patients over 65 years of age, who, particularly after AVR, have experienced ≥98% freedom from SVD at 20 years. 3,4 The MB incorporates some features aimed at improving durability. Chief among these is the use of α-amino oleic acid, because this anticalcification treatment has been extremely effective in mitigating cusp calcification in animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies from North America and Europe have reported excellent clinical outcomes after aortic valve replacement (AVR) with either the Hancock II or the Perimount. [1][2][3][4][5][6][7] The Medtronic Hancock II offers 10-and 15-year survival ranging from 63% to 67% and 35% to 47%, respectively. [1][2][3][4] The Perimount performs similarly, with 10-and 15-year survival ranging from 53% to 69% and 35% to 68%, respectively.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The Medtronic Hancock II offers 10-and 15-year survival ranging from 63% to 67% and 35% to 47%, respectively. [1][2][3][4] The Perimount performs similarly, with 10-and 15-year survival ranging from 53% to 69% and 35% to 68%, respectively. [5][6][7] Reported freedom from structural valve deterioration, reoperation, prosthetic valve endocarditis, and thromboembolism are favorable after AVR with either the Hancock II or the Perimount.…”
mentioning
confidence: 99%